Entas-Entas Etnoritual in Tengger Village Ngadas Kidul Poncokusumo Subdistrict Malang - Jati Batoro (Natural B, Journal of Health and Environmental Sciences, 2011)
The aim of this research was to study and investigate the various plants and animals to used for ritual Entas-entas, Tengger society in Ngadas Kidul village, subdistrict of Poncokusumo, residence of Malang, East Java. This research methods was included structural and open ended discussion and direct observation with follow ceremonial ethnoritual from Petinggi Tengger, Dukun Pandhita (master of ritual), wong Sepuh, Legen and Tengger people. The result of this research showed that the ethnoritual Entas-entas was still good and consistency special in Ngadas Kidul, central Tengger area. Sum of plants to used in ritual involved 30 species and 6 species of animals; 3 species of mammals  and 3 species of aves.